Catalytic upgrade for pyrolysis of food waste in a bubbling fluidized-bed reactor. (15th April 2021) - Ly, Hoang Vu; Tran, Quoc Khanh; Kim, Seung-Soo; Kim, Jinsoo; Choi, Suk Soon; Oh, Changho
Abstracts: Biofuel production via pyrolysis has received increasing interest as a promising solution for utilization of now wasted food residue. In this study, the fast pyrolysis of mixed food waste (MFW) was performed in a bubbling fluidized-bed reactor. This was done under different operating conditions (reaction temperatures and carrier gas flow rate) that influence product distribution and bio-oil composition. The highest liquid yield (49.05 wt%) was observed at a pyrolysis temperature of 475 °C. It was also found that the quality of pyrolysis bio-oils (POs) could be improved using catalysts. The catalytic fast pyrolysis of MFW was studied to upgrade the pyrolysis vapor, using dolomite, red mud, and HZSM-5. The higher heating values (HHVs) of the catalytic pyrolysis bio-oils (CPOs) ranged between 30.47 and 35.69 MJ/kg, which are higher than the HHVs of non-catalytic pyrolysis bio-oils (27.69–31.58 MJ/kg). The major components of the bio-oils were fatty acids, N-containing compounds, and derivatives of phenol. The selectivity for bio-oil components varied depending on the catalysts. In the presence of the catalysts, the oxygen was removed from oxygenates via moisture, CO2, and CO. The CPOs contained aliphatic hydrocarbons, polycyclic aromatic compounds (such as naphthalene), pyridine derivatives, and light oxygenates (cyclic alkenes and ketones). Graphical abstract: Image 1 Highlights: Bio-oils upgraded by catalytic pyrolysis with catalysts showed high HHV. Dolomite promoted the thermal cracking and increased H2 and hydrocarbon gas. HZSM-5 improved decarbonylation and the generation of aromatic compounds. Red mud promoted the decarboxylation and formation of alkanes, alkene. The upgraded bio-oil with high fractions of C5 ∼C18 was suitable for green fuel.